Urban-rural difference in the costs of disability and its effects on poverty among people with disabilities in China - Juan Liao; Qi Wang; Jin-Ling Huang; Ya-Min Wei (Frontiers Media S.A., 2022)
The urban-rural difference in poverty is an important issue in China, particularly for people with disabilities. The extra costs of disability render this population susceptible to falling into poverty, where this can exacerbate the inequality among people with disabilities between urban and rural areas of the country. Previous studies have provided empirical evidence for the extra costs of disabilities in certain countries, but little scholarly attention has been devoted to the urban-rural gap in the costs of disability, particularly in countries like China that have a dual urban-rural system. This study explores changes in the extra costs of disability in China between urban and rural households with disabled members from 2008 to 2018 by using the standard of living approach. We apply the Foster-Greer-Thorbecke Poverty Index to measure the rates of poverty in urban and rural households with disabilities after considering the costs of disability. The results reveal that the costs of disability were not always lower for rural households than for urban households. At the same time, many rural households with disabled people were found to suffer from severe poverty owing to the high costs of their disabilities. The difference in health insurance and rehabilitation services between urban and rural China have led to an urban-rural gap in the costs of disability. This suggests that supplying more goods and services for disabled people in rural areas, especially free services, and raising the reimbursement due to them from their health insurance can help improve their standard of living.